Isolation, Characterization, and Inactivation of Stenotrophomonas maltophilia From Leafy Green Vegetables and Urban Agriculture Systems - Li, Dan; Wong, Chun Hong; Seet, Mei Fang; Kuan, Nicole (Frontiers in Microbiology, 2019)
Stenotrophomonas maltophilia is an emerging opportunistic pathogen which on one hand can cause severe nosocomial infection for immunocompromised population with a high mortality rate, on the other hand can be present ubiquitously in the environment. This study, for the first time to the best of our knowledge, investigated the presence and characteristics of S. maltophilia from leafy green vegetables produced by hydroponic farms as well as a hydroponic farming facility in Singapore. Eleven S. maltophilia isolates were obtained from three types of leafy green vegetables (sweet basil, kale, and parsley) and the nutrient solution used by a hydroponic farm. The antimicrobial resistance, biofilm forming ability, resistance to UV and quatenary ammonium compounds (QAC) treatments, as well as the fate of S. maltophilia in simulated leafy green vegetable environment during a storage period of 6 days at different temperatures were investigated. According to our results, high population levels of S. maltophilia could be reached both in leafy green vegetables especially after being stored at abused temperatures (>8-log CFU/ml in basil juice after 6 days storage at 20°C) and on hydroponic farming facilities probably due to biofilm formation (8 to 9-log CFU/well in biofilms). UV treatment, which could induce substantial reductions of S. maltophilia presence in both single-species and dual-species biofilms mixed with Salmonella enterica serovar Typhimurium reference strain (ATCC 14028) or self-isolated Pseudomonas fluorescens (>4-log reductions by 250 mJ/cm2 UV), is recommended to be employed by hydroponic farms to treat their nutrient solutions and farming facilities to enhance the microbial safety.